STRATEGI USAHA KECIL MENENGAH PENJUAL SEMBAKO DI DESA KUBUTAMBAHAN DALAM MENINGKATKAN KEUNTUNGAN - Kadek Dena Krisnantara; Mertyani Sari Dewi (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Economic activity is an effort to increase the power and standard of living of the community due to increased economic growth and the increasing needs of the community. In order to meet the needs of life in order to be prosperous, people who have the ability and are observant to see their potential and are able to identify the environment, can find opportunities and open up business opportunities for the community through entrepreneurship. In Kubutambahan Village, there are many retail traders who have the potential to increase their business profits. One example of a basic food trader is KUD. Karma Bumi Amertha. KUD. Karma Bumi Amertha is a cooperative that was founded on the principle of kinship with the aim of helping community activities in Kubutambahan Village.This type of research is a qualitative research that seeks to collect facts and circumstances properly through interviews. The interview technique used is a structured interview conducted with KUD Karma Bumi Amertha resource persons are business owners, employees, and consumers.The results obtained indicate that the business prospects of selling groceries at KUD. Karma Bumi Amertha has increased through the strategy implemented, namely the Generic Whelen Hunger Strategy. This strategy is very effective for KUD. Karma Bumi Amertha because it plays a very important role in increasing income.